Kinetic and in vitro ruminal fermentation characteristics of copra meal diets with different fat levels - Lima, Talma Jordana; De Paula, Talita Almeida; De Souza Castagnino, Pablo [UNESP]; De Almeida Teixeira, Izabelle Auxiliadora Molina [UNESP]; Beelen, Roger Nicolas; Beelen, Patricia Mendes Guimarães (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2017)
This study aimed at evaluating the chemical composition and in vitro ruminal characteristics of diets using copra meal with different fat contents. Three levels of copra meal inclusion (10, 20 and 30%) and two levels of fat (high-fat copra meal - HFCM and low-fat copra meal - LFCM) were used in replacement of soybean meal. The addition of copra meal increased EE and reduced CP and NFC of diets, especially when HFCM was included. Treatments with the inclusion of 30% copra meal had a higher colonization time (L), independently of fat content. The maximum gas production was reduced from 59.06 to 39.21 mL/g DM with the addition of HFCM, but was not affected when diets contained LFCM. Digestibility was also reduced with the addition of copra meal, the highest reduction being with the addition of 30% copra meal. Copra meal inclusion has reduced the ammonia concentration from 29.75 mg/100 mL (control diet) to 17.05 mg/100 mL (30% copra meal) but did not affect significantly methane production. Copra meal impacts the chemical composition and ruminal fermentation characteristics of diets, especially when containing high oil content.
Keywords: Byproduct; Coconut oil; Methane mitigation